The Merchant Bourgeoisie Fighting for Liberal Economy: Discussions on Tobacco Monopoly in the First Decade of the Republic of Turkey - Basaran Lotz, Neslisah Leman (Journal of Applied And Theoretical Social Sciences, 2022)
This article is about the discussions on the tobacco business in Turkey after the abolishment of the monopoly of the private French Régie Company on tobacco in 1923. In these discussions which continued throughout the 1920’s, the Turkish merchants led a campaign to put pressure on the government to introduce a system of free trade and free market in tobacco business. By analyzing these discussions on tobacco monopoly, the article aims to reveal the nature of the relations between the relatively new business class in the country and the rulers of the newly build Turkish Republic. Since Turkey is a late developed capitalist economy, the origins and development of its capitalist class has always been an issue of discussion. The article tries to demonstrate that the Turkish businesspersons possessed the capacities and means of guiding and confronting the political government in the early years of the republican period. It argues that the campaign on tobacco organized by Turkish merchants proves their organization capacities to defend their common interest and that these businesspersons deserve to be called as the merchant bourgeoisie of the country.